Effect of clarified Brazilian native fruit juices on postprandial glycemia in healthy subjects - Balisteiro, Diully Mata; Araujo, Renata Luise de; Giacaglia, Luciano Ricardo; Genovese, Maria Inés (Food research international, 2017)
Brazilian native fruits have been shown as excellent sources of polyphenols which are associated with multiple biological activities including inhibition of carbohydrate-hydrolyzing enzymes, α-amylase and α-glucosidase. Postmeal blood glucose elevations and high glycemic index diets can play a major role in the development of type 2 diabetes, therefore alternative approaches to reduce postprandial hyperglycemia are of growing interest in order to reduce diabetes risk. Here we investigated the effect of six Brazilian native clarified fruit juices from Amazon, Savannah and Atlantic Forest biomes on postprandial glycemia after consumption of a carbohydrate meal. For this, 23 healthy subjects were selected to consume seven meal tests, with a 1-week interval among them, consisting in 50g white bread plus 300mL of water (control) or cambuci, cagaita, maracujá-alho, cupuaçu, camu-camu and jaboticaba clarified fruit juices. The results showed that serum glucose concentrations were significantly lower after consumption of cambuci, cagaita, camu-camu and jaboticaba juices, whereas maracujá-alho and cupuaçu juices did not decrease the amount of glucose absorbed, compared to control (p<0.05). In addition, cagaita, cambuci, cupuaçu and jaboticaba juices increased the oxygen radical absorbance capacity in plasma, whereas all juices augmented the ferric reducing ability of plasma, except for cambuci (p<0.05). These results indicate that juices from Brazilian native fruits may be considered as adjuvant treatment for reduction of postprandial glycemia in healthy subjects. [Display omitted] •Brazilian fruits are sources of polyphenols with potential antidiabetic properties.•Fruit juices consumption decreased postmeal glucose absorption in healthy subjects.•Postprandial glucose response decreased from 11% to 64% after consumption of juices.